1998
DOI: 10.1021/bi981291f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Kinetic Mechanism of Catalytic Domain of Human Vascular Endothelial Growth Factor Receptor-2 Tyrosine Kinase (VEGFR2 TK), a Key Enzyme in Angiogenesis

Abstract: Vascular endothelial growth factor (VEGF) is a dimeric protein which induces formation of new blood vessels (angiogenesis) through binding to VEGF-receptor-2 tyrosine kinase (VEGFR2 TK) or KDR (kinase insert domain-containing receptor) on the surface of endothelial cells. Angiogenesis has been shown to be essential for malignancy of tumors; therefore, VEGFR2 TK is a potential therapeutic target for the treatment of cancer. Sequence homology studies indicate that VEGFR2 TK contains three domains: extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 39 publications
6
56
0
Order By: Relevance
“…This model describes the kinetic data extremely well and describes a situation where the interconversion of ternary complexes is rate-limiting. The rapid-equilibrium model has been proposed for other protein kinases such as c-Src (39) and kinase insert domain receptor (40). However, product inhibition data are not definitive evidence for a rapid-equilibrium mechanism, because experimental error can hide subtle differences predicted for some non-equilibrium mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This model describes the kinetic data extremely well and describes a situation where the interconversion of ternary complexes is rate-limiting. The rapid-equilibrium model has been proposed for other protein kinases such as c-Src (39) and kinase insert domain receptor (40). However, product inhibition data are not definitive evidence for a rapid-equilibrium mechanism, because experimental error can hide subtle differences predicted for some non-equilibrium mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For cAMPdependent kinase Whitehouse et al (50,51) reported that the mechanism was ordered, with the nucleotide binding first while Cook et al (30) reported that MgATP and peptide bind randomly, although initial binding of the nucleotide is preferred. An ordered sequential mechanism has been reported for p38 MAPK (32), for the vascular endothelial growth factor receptor-2 tyrosine kinase (52) and for the v-Src kinase (53). Both an ordered (54) and a random pathway (55) have been reported for the EGF receptor tyrosine kinase.…”
Section: Table II Summary Of Kinetic Constantsmentioning
confidence: 95%
“…Biochemical characterization of RTKs has been performed using both recombinant truncated kinase domains and cytoplasmic domains (5,(11)(12)(13)(14). Cheng and Koland (14) showed that the cytoplasmic domain of the EGF receptor has an almost 10-fold greater K d for an ATP analog than a carboxyl terminus deletion mutant of the cytoplasmic tail (14), demonstrating that the isolated kinase domain may not be a sufficient model for receptor function.…”
Section: Stimulation Of Receptor Tyrosine Kinases (Rtks)mentioning
confidence: 99%
“…Studies with polyclonal antibodies have qualitatively shown that a phosphorylated monomeric receptor does not possess the ability to phosphorylate exogenous substrate in the same manner as the oligomeric receptor (8). All of these studies would indicate that there is some unique functional characteristic contained within the oligomeric RTK that is not present in the monomeric receptor.Biochemical characterization of RTKs has been performed using both recombinant truncated kinase domains and cytoplasmic domains (5,(11)(12)(13)(14). Cheng and Koland (14) showed that the cytoplasmic domain of the EGF receptor has an almost 10-fold greater K d for an ATP analog than a carboxyl terminus deletion mutant of the cytoplasmic tail (14), demonstrating that the isolated kinase domain may not be a sufficient model for receptor function.…”
mentioning
confidence: 99%